Analysis of hydrogen production by anaerobic fermentation from urban organic waste (2015)
The production of hydrogen by anaerobic fermentation of urban organic waste from fruits and vegetables was studied. Ten tests were carried out under an incomplete factorial experiment design with four factors and three levels. The factors were: acidification pH, acidification time, operational pH, and organic load. The response variables were: maximum hydrogen content (%) and maximum hydrogen production (L/day). The results were fitted to a quadratic polynomial model. In the case of the maximum hydrogen content, an R2 and an R2adjusted of 0.9987 and 0.988 were obtained, respectively. For the maximum production, an R2 and an R2adjusted of 0.9815 and 0.833 were obtained, respectively. Three mathematical techniques were used to obtain the maximum values in the response variables. Fuzzy logic showed the best fit between the experimental values and estimated values. In addition, it predicts a maximum hydrogen content of 58.5% and a maximum production of 63.4 L/day.